2016
DOI: 10.5194/nhess-16-595-2016
|View full text |Cite
|
Sign up to set email alerts
|

The European lightning location system EUCLID – Part 1: Performance analysis and validation

Abstract: Abstract. In this paper we present a performance analysis of the European lightning location system EUCLID for cloud-to ground flashes/strokes in terms of location accuracy (LA), detection efficiency (DE) and peak current estimation. The performance analysis is based on ground truth data from direct lightning current measurements at the Gaisberg Tower (GBT) and data from E-field and video recordings. The E-field and video recordings were collected in three different regions in Europe, namely in Austria, Belgiu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 18 publications
5
153
0
1
Order By: Relevance
“…ALDIS is part of the European cooperation for lightning detection (EUCLID) (Pohjola and Mäkelä, 2013;Schulz et al, 2016), which bundles European efforts in lightning detection. Schulz et al (2016) present an evaluation of the performance of lightning detection in Europe and the Alps by comparison against direct tower observations with respect to detection efficiency, peak current estimation and location accuracy.…”
Section: Datamentioning
confidence: 99%
“…ALDIS is part of the European cooperation for lightning detection (EUCLID) (Pohjola and Mäkelä, 2013;Schulz et al, 2016), which bundles European efforts in lightning detection. Schulz et al (2016) present an evaluation of the performance of lightning detection in Europe and the Alps by comparison against direct tower observations with respect to detection efficiency, peak current estimation and location accuracy.…”
Section: Datamentioning
confidence: 99%
“…Data from the lightning information service "BLitz InformationDienst Siemens" (BLIDS), which is part of the EUropean Cooperation for LIghtning Detection network (EUCLID; Schulz et al, 2016;Drüe et al, 2007), were used to ensure that wind measurements were related to thunderstorm events. We considered only the time and location of the lightning, whereas polarity and power information were neglected.…”
Section: Lightning Datamentioning
confidence: 99%
“…In addition, Schulz et al (2016) showed that the LA dropped steadily over the years down to the present LA in the range of 100 m within the majority of the network. Note that in Schulz et al (2016) ground-truth observations are collected in Austria and Belgium, the same regions of the EUCLID network which are studied in this paper.…”
Section: Lightning Location Datamentioning
confidence: 94%
“…To retrieve the latter values, only those strokes that match certain quality criteria such as χ 2 are used in the analysis, which is a measure for the agreement between the different sensor measurements and the semi-major axis (SMA) of the confidence ellipse, and received a correct stroke classification as CG by the central processor. Those strict criteria, as well as temporary sensor outages during the measurements campaign, can impact the DE estimates given in Schulz et al (2016). In addition, Schulz et al (2016) showed that the LA dropped steadily over the years down to the present LA in the range of 100 m within the majority of the network.…”
Section: Lightning Location Datamentioning
confidence: 99%
See 1 more Smart Citation